The effect of project-based learning model to improve the ability of HOTS on science in elementary school - Ririn Andriani Kumala Dewi; Eni Qurotul A'eni; Tommy Tanu Wijaya (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2023)
This study aims to prove whether the effect of project-based learning model to improve the ability of Higher Order Thinking Skill (HOTS) on science learning in grade IV Elementary School. The method used is truly experimental, the form of the design is a pretest-posttest control group design. The sample used in this study is the students of class IV amounted to 52 students and divided into two classes, the sample used in this study is the students of class IV amounted to 52 students and divided into two classes, i.e., class IV A as an experiment class and class IV B as control class. As a test data collection technique is a multiple-choice question sheet, a description sheet, and a questionnaire sheet. The data analysis technique used is a t-test calculation and normalized gain test. The results of this study using t-tests indicate that there is a Higher Order Thinking Skill (HOTS) influence of students between the control class and the experiment class. The results of the research using normalized gain test showed that there was an increase Higher Order Thinking Skill (HOTS) after applying a project-based learning model in the experiment class. The student's response to project-based learning model is applied that students provide positive responses. Based on data analysis, it is proven that the application of project-based learning model has a positive effect on the improvement of the higher order thinking skill (HOTS) in the IPA IPA classroom elementary school. Pengaruh model pembelajaran berbasis proyek untuk meningkatkan kemampuan HOTS IPA di sekolah dasarPenelitian ini bertujuan untuk membuktikan ada tidaknya pengaruh model pembelajaran berbasis proyek terhadap peningkatan kemampuan higher order thinking skill (HOTS) pada mata pelajaran IPA di kelas IV Sekolah Dasar. Metode yang digunakan adalah metode penelitian eksperimen murni, bentuk design adalah Pretest-Posttest Control Group Design. Sampel yang digunakan dalam penelitian ini adalah siswa kelas IV yang berjumlah 52 siswa dan terbagi ke dalam dua kelas, Sampel yang digunakan dalam penelitian ini adalah siswa kelas IV yang berjumlah 52 siswa dan terbagi ke dalam dua kelas, yaitu kelas IV A sebagai kelas eksperimen dan kelas IV B sebagai kelas kontrol. Teknik pengumpulan data tes adalah lembar soal pilihan ganda, lembar soal uraian dan lembar angket. Teknik analisis data yang digunakan adalah perhitungan uji-t dan uji gain ternormalisasi. Hasil penelitian ini dengan menggunakan uji-t menunjukkan bahwa terdapat pengaruh higher order thinking skill (HOTS) siswa antara kelas kontrol dan kelas eksperimen. Hasil penelitian dengan menggunakan uji gain ternormalisasi menunjukkan bahwa terdapat peningkatan kemampuan higher order thinking skill (HOTS) siswa setelah diterapkan model pembelajaran berbasis proyek pada kelas eksperimen. Adapun tanggapan siswa terhadap model pembelajaran berbasis proyek yang diterapkan yaitu siswa memberikan tanggapan yang positif. Berdasarkan analisis data, terbukti bahwa penerapan model pembelajaran berbasis proyek berpengaruh positif terhadap peningkatan kemampuan higher order thinking skill (HOTS) pada pelajaran IPA kelas IV Sekolah Dasar.